Essential Oil Profile of Areal Part of Datura stramonium L. and D. innoxia from Iran - Zahra Morovati; Ghasem Karimzadeh; Mohammad Reza Naghavi; Sajad Rashidi Monfared (Agrotechniques in Industrial Crops, 2023)
The chemical constituents of essential oils of Datura stramonium L. and D. innoxia (family Solanaceae) are being reported. In this study, the collected seeds of Ardabil and Urmia were planted in grow bags and placed for three months in a greenhouse of the College of Agriculture, Tarbiat Modares University in Tehran. Under greenhouse conditions, the average air temperature was 25 °C. Air-dried areal parts of D. stramonium and D. innoxia were prepared and their essential oils (EOs) were isolated by hydrodistillation for 3 h in a Clevenger-type apparatus. EOs content and composition were examined with gas chromatography techniques. The EOs yield of D. stramonium and D. innoxia were 0.03% and 0.02% (v/w), respectively. The major compounds in the D. stramonium EOs were Camphor (29.9%), Selin-11-en-4alpha-ol (13.0%), and Borneol (10.4%). Those in the D. innoxia were mostly fatty alkanes, including n-Decane (19.99%), 7-Pentadecyne (11.78%), and Linoleic acid (6.13%). The other important components identified in the EOs of Datura were Dihydrocitronellol, n-Dodecane, Isobornyl acetate, Germacrene D, and n-Tetradecane. Generally, the EOs of the areal parts in D. stramonium showed oxygenated monoterpenes.